The relationship between oxidative stress marker and atherosclerosis in diabetes hyperlipidemic patient - Kareem Esmat, Sura Abdul; Rijab, Hiba Ghassan; Al-sabea, Najeeb Butrus (International Journal of Psychosocial Rehabilitation, 2020)
Diabetes mellitus can defined as disease characterized by many metabolic abnormalities like increased in blood glucose level (hyperglycemia) and failure in either synthesis or action of insulin that synthesized in the body by β-cell of pancreas, this disease accompanied by high mortality and morbidity due to the high percentage of exposure to cardiovascular complications (CVD). Seventy five people included in this study, all from Al-Kadhmiya Teaching Hospital during period from December 2019 to February 2020, study design (case –control study). Subjects were divided into two groups: 1- Control group (non- patient group): involve 50 healthy subjects 2-Patient study group: involve 25 diabetic hyperlipidemic subjects. All patients were diagnosed with hyperglycemia have Fasting blood sugar (FBS 125 – 300 mg/dl) with age between ( 40 – 65 years) and BMI (29.8% – 33%) and suffering of dyslipidemia; while control group have (FBS 74 – 120 mg/dl) and with age between ( 40 – 65 years) and BMI ( 28% - 31%)with normal lipid profile. There was significantly increasing in mean value of HbA1c, lipid profile, CRP and glutathione peroxidase in diabetic patient group than healthy control people (p<0.001) We can conclude that accelerated factors of atherosclerosis in diabetic patients is hyperglycemia in addition to dyslipidemia and increasing oxidative stress that lead to production of inflammatory factors and promote inflammatory reaction with blood vessels wall. Diabetic hyperlipidemic vasculature is a key mediator for atherosclerosis